Power flow stabilization and control of microgrid with wind generation by superconducting magnetic energy storage - Molina, Marcelo Gustavo (2011)
High penetration of renewable energy sources such as wind generation in microgrids (MGs) causes fluctuations of power flow and significantly affects the power system (PS) operation. This can lead to severe problems, such as system frequency oscillations, and/or violations of power lines capability. With the proper control, superconducting magnetic energy storage (SMES) is able to significantly enhance the dynamic security of the PS. In an SMES system, the power conditioning system (PCS) is the crucial component that directly influences the validity of the SMES in the dynamic control of the PS. This paper proposes the use of an improved SMES controller for the stabilization and control of the power flow of wind-hybrid MGs. In this sense, the design and implementation of a novel high-performance PCS scheme of the SMES is described. Moreover, a detailed model of the SMES unit is derived and a novel three-level control scheme is designed, comprising a full decoupled current control strategy in the d-q reference frame and an enhanced PS frequency controller. The dynamic performance of the proposed systems is fully validated by computer simulation.